Avaliação físico-química das águas superficiais da bacia do Paracuri, Belém - PA - PARAENSE, Rafaela Maritha Araújo (2020)
The Paracuri watershed, located in the expansion zone of the municipality of Belém, has suffering a disorderly urbanization process. The deficiency of sewage stations in the peripheral regions poses a great risk to the water quality. Therefore, this study promoted a monitoring of the surface waters of the Paracuri watershed, located in the Metropolitan Region of Belém. Six surface water samples were collected during four sampling campaigns, during the dry and rainy seasons of the region. The sampling points were distributed preferentially near the river mouth of the Paracuri and Livramento streams, the convergence region where all the effluents discharges into, and it is located near commerce, residences and navigation ports. The physicochemical parameters approached in this research were compared with the limits established by Resolution No. 357 of 2005 of the Conselho Nacional do Meio Ambiente (CONAMA), for class 2 freshwater, and correlated with possible sources with natural or anthropic origin. Temperature, pH, total dissolved solids, ammonia, zinc, barium, copper, arsenic, nickel and lead were in accordance with Brazilian law. It was noted that climatic conditions influences directly some parameters, such as iron, aluminum, manganese, arsenic and heavy metals contents, which present higher concentrations during the rainy season, due to the remobilization of the sediments by rainwater, which also results in increased turbidity during this period. The highest values of electrical conductivity, and by correlation, of total dissolved solids occur due to the ion concentration, mainly sodium and to a lesser extent calcium, magnesium and potassium, higher during the dry season. In addition, analyses of properties such as alkalinity and hardness showed that these waters are more resistant to pH changes in the rainy season, when they have higher alkalinity, and that can be classified as “soft water”, due to the CaCO3 concentration. The main parameters that indicated alteration of water quality due to anthropic influence were anionic surfactants (AS) and iron. AS concentrations exceeded up to 36 times the limit established by law, which indicates discharge of domestic and industrial effluents directly into these water resources. The iron, which had levels above the legislation in three sampling campaigns, may come from the shipping ports and shipyards that exist in that region.